Challenges of Majelis Da'wah in Strengthening Santri Culture at Islamic Boarding Schools - Jauhari, Ali (Journal of Modern Islamic Studies and Civilization, 2023)
This study aims to describe the opportunities and challenges of implementing halaqah da'wah in building the religious and honest character of the santri. This type of research is descriptive qualitative research with the main data source being students as informants, murabbi as key informants and the chairman of the foundation as extend informant. Documents, journals, and books become secondary data. Collecting data with in-depth interview techniques, observation and documentation. Data analysis techniques were carried out by meducing data, presenting and drawing conclusions. What was obtained from this study showed that the opportunities and challenges were not only felt by the students, the murabbi and the Islamic boarding school also felt them. Santri have the opportunity to add additional insight related to adab and religious aqeedah. On the other hand, challenges in the form of feeling tired and drowsy after will activities reduce their concentration in carrying out Da'wah halaqah. The results of this study become a reference for Islamic boarding schools in managing schedules for efficient implementation of halaqah Da'wah. Integrating Islamic values through preaching halaqah is an alternative solution to learning models in public schools so that the values of the younger generation are not distracted by the times.